2021
DOI: 10.1200/jco.2021.39.15_suppl.506
|View full text |Cite
|
Sign up to set email alerts
|

Durvalumab improves long-term outcome in TNBC: results from the phase II randomized GeparNUEVO study investigating neodjuvant durvalumab in addition to an anthracycline/taxane based neoadjuvant chemotherapy in early triple-negative breast cancer (TNBC).

Abstract: 506 Background: The GeparNuevo trial investigated the addition of durvalumab, an anti-PD-L1 checkpoint inhibitor (CPI), to standard neoadjuvant chemotherapy (NACT) in patients with early TNBC. Durvalumab increased the pathological complete response (pCR) rate particularly in patients treated with durvalumab alone before start of chemotherapy (Loibl et al. Ann Oncol 2019). Methods: GeparNuevo randomized patients with cT1b-cT4a-d tumors and centrally confirmed TNBC to durvalumab (D) 1.5 g i.v. or placebo every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 0 publications
3
82
0
3
Order By: Relevance
“…In the recently reported KEYNOTE-522 study (NCT03036488) 5 , pembrolizumab, a PD-1 inhibitor, was found to significantly but moderately increase the rates of pathological complete response (pCR) and significantly improve event-free survival (EFS) when added to a neoadjuvant regimen of anthracycline, taxanes and carboplatin in patients with stage II and III TNBC. Similar magnitude of EFS improvements have been reported in smaller studies 6 , 7 . PD-L1 protein is known to be highly expressed on the breast cancer TIL and correlations between both markers have been observed 8 .…”
Section: Introductionsupporting
confidence: 87%
“…In the recently reported KEYNOTE-522 study (NCT03036488) 5 , pembrolizumab, a PD-1 inhibitor, was found to significantly but moderately increase the rates of pathological complete response (pCR) and significantly improve event-free survival (EFS) when added to a neoadjuvant regimen of anthracycline, taxanes and carboplatin in patients with stage II and III TNBC. Similar magnitude of EFS improvements have been reported in smaller studies 6 , 7 . PD-L1 protein is known to be highly expressed on the breast cancer TIL and correlations between both markers have been observed 8 .…”
Section: Introductionsupporting
confidence: 87%
“…Finally, durvalumab (Imfinzi) combined with neoadjuvant anthracycline and taxane-based chemotherapy substantially improved survival rates in patients with early TNBC, according to GeparNUEVO phase II trial, as announced in the 2021 American Society of Clinical Oncology (ASCO) Annual Meeting. The findings of the trial showed that patients in the durvalumab arm obtained a complete response of 53.4% compared to 44.2% of patients in the placebo arm [36].…”
Section: Pd-l1 Protein -Immune Checkpoint Inhibitorsmentioning
confidence: 97%
“…In comparison to tumors such as melanoma and lung, immunotherapy in breast cancer has only shown a modest benefit in certain subsets of patients. Initial studies with ICI monotherapy in advanced triple negative breast cancer (TNBC) showed disappointing results [ 1 , 2 , 3 ], necessitating combination therapy with other neoplastic agents [ 4 , 5 ]. Currently, the FDA has approved pembrolizumab in two indications for the treatment of breast cancer based on results of phase III clinical trials combining it with standard of care chemotherapy in a subset of patients with TNBC [ 4 , 6 ].…”
Section: Immune Checkpoint Inhibition In Breast Cancermentioning
confidence: 99%